PENGARUH DANA BANTUAN PENDIDIKAN, ANGKA PARTISIPASI SEKOLAH DAN PENGANGGURAN TERBUKA TERHADAP KEMISKINAN DI SUMATERA - Putri Rahmayani; Devi Andriyani (Jurnal Ekonomi Regional Unimal, 2022)
This study aims to determine the effect of education assistance funds, school participation rates, and open unemployment on the poverty in Sumatra for the 2015-2019 period. The data used in this study are secondary data with a cross section of 10 provinces in Sumatra and time series data with a time period of 2015-2019. The data analysis method used panel data regression. The results showed that partially the education assistance fund variable had no significant and negative effect on the poverty level variable in Sumatra, the school participation rate variable had no significant and positive effect on the poverty in Sumatra, the open unemployment variable had a significant effect. and positive for the variable poverty in Sumatra. The results of the study simultaneously show that the variable education assistance funds, the school participation rate variable, and the open unemployment variable significantly influence the poverty variable in Sumatra.